The Gap Between Program Planning and Implementation: The Case of R&D Program in Indonesian RPJMN - Budi Triyono; Ria Hardiyati; Aditya Wisnu Pradana (STI Policy and Management Journal, 2020)
This article attempts to analyze various obstacles related to the minimal contribution of Indonesian R&D Program in supporting the economic sector and national competitiveness. This was done through a review of the implementation of the document of the National Medium-Term Development Plan (RPJMN) in the S&T Sector for 2015‒2019 periode. The analysis was carried out using the Grindle policy implementation model. The study shows that there are four main factors that hinder the implementation of the R&D program, such as 1) the lack of integration of R&D execution between LPNK and technical ministries, 2) R&D program planning which tends to be technology supply-push, 3) the absence of an appropriate evaluation mechanism to measure the achievement research in support of the economic sector, and 4) limited on research budget resources and its diffusion.